From Trauma to Reconstruction: Insights from Penile Amputation Case Series. - Mangende, Vebryanti Riki; Adi, Kuncoro (Journal of Neonatal Surgery, 2026)
Background: Traumatic penile amputation is a rare but severe urological emergency caused by self-mutilation, accidents, circumcision, or assault. Recent advancements in microvascular techniques have improved the success rate of penile reimplantation, reducing the need for penectomy and minimizing postoperative complications. This study presents a case series on penile amputation management and reviews the latest literature to explore optimal treatment strategies. Case Presentation: This series includes two cases of pediatric penile trauma. Case 1 involved an 8-year-old with penile strangulation by hair, leading to necrosis and a urethrocutaneous fistula. The patient underwent debridement and reconstruction, with a favorable postoperative outcome. Case 2 described a 10-year-old with AAST Grade V penile amputation during cautery circumcision. The injury was managed through reimplantation and anastomotic urethroplasty, resulting in functional recovery. Conclusion: Penile amputation significantly impacts both physical and psychological health. This series highlights the importance of microvascular anastomosis as the preferred replantation method for preserving erectile and voiding function. Advanced reconstructive techniques and interdisciplinary care, including mental health support, are essential for improving outcomes in complex cases..